Molecular detection of goat and sheep meat origin using mitochondrial cytochrome b gene - Jahura, FT; Munira, S; Bhuiyan, AKFH; Hoque, MR; Bhuiyan, MSA (Bangladesh Journal of Animal Science, 2016)
The present study was conducted to discriminate between sheep and goat species meat origin utilizing mitochondrial cytochrome b (Cyt b) gene fragment. A total of 46 ear tissue and meat samples were collected from different slaughterhouses and farms of Mymensingh and Rangpur districts. Genomic DNA was extracted using GeNet Bio DNA isolation kit and DNA concentration and purity was quantified by NanoDrop spectrophotometer. Two pairs species specific primer were used to amplify Cyt b gene fragments. Selected primers were highly conserved across the breed within a species and worked well with the species of indigenous goat and sheep resulting similar size of the amplicons 330 and 585 bp respectively. The duplex PCR condition would enable to detect adulteration from goat and sheep mixed samples which revealed by two precise bands (330 and 585 bp) in a single reaction. This study suggests an accurate molecular technique for identification of sheep and goat meat species origin and differentiates species present in adulterate meat samples. In conclusion, this DNA based marker could be used for prevention of fraudulent practice in slaughterhouse and chain shops in Bangladesh. Bang. J. Anim. Sci. 2016. 45 (2): 41-45